Photocatalytic decomposition of methylene blue via Fenton mechanisms by silicon wafer doped with Au and Cu: a theoretical and experimental study - Ramalho, Teodorico C.; Carvalho, Hudson W. P.; Batista, Ana P. L.; Perez, Carlos A.; Gobbi, Angelo L. (Springer, 2009)
In this work, we studied the photocatalytic and the structural aspects of silicon wafers doped with Au and Cu submitted to thermal treatment. The materials were obtained by deposition of metals on Si using the sputtering method followed by fast heating method. The photocatalyst materials were characterized by synchrotron-grazing incidence X-ray fluorescence, ultraviolet-visible spectroscopy, X-ray diffraction, and assays of H(2)O(2) degradation. The doping process decreases the optical band gap of materials and the doping with Au causes structural changes. The best photocatalytic activity was found for thermally treated material doped with Au. Theoretical calculations at density functional theory level are in agreement with the experimental data.